2004
DOI: 10.1091/mbc.e03-06-0432
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in the Normal Adult Human Kidney Assessed by Complementary DNA Microarray

Abstract: The kidney is a highly specialized organ with a complex, stereotyped architecture and a great diversity of functions and cell types. Because the microscopic organization of the nephron, the functional unit of the kidney, has a consistent relationship to the macroscopic anatomy of the kidney, knowledge of the characteristic patterns of gene expression in different compartments of the kidney could provide insight into the functions and functional organization of the normal nephron. We studied gene expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 51 publications
4
94
0
4
Order By: Relevance
“…To enable this analysis, we performed crossmapping of kidney and kidney-compartment-specific genes obtained from microdissected compartments of normal kidney by profiling these tissues on cDNA microarrays with protoarray protein targets, using our published approach of integrated antibiomics. 18,21,22 This analysis revealed that there was an enrichment for antigens expressed in the renal cortex (P=0.029). As previously shown, the renal pelvis antigens are highly immunogenic, and enrichment for pelvis-specific antigens was also noted.…”
Section: Cross-mapping Cai-specific Non-hla Antibodies To Expressionmentioning
confidence: 90%
“…To enable this analysis, we performed crossmapping of kidney and kidney-compartment-specific genes obtained from microdissected compartments of normal kidney by profiling these tissues on cDNA microarrays with protoarray protein targets, using our published approach of integrated antibiomics. 18,21,22 This analysis revealed that there was an enrichment for antigens expressed in the renal cortex (P=0.029). As previously shown, the renal pelvis antigens are highly immunogenic, and enrichment for pelvis-specific antigens was also noted.…”
Section: Cross-mapping Cai-specific Non-hla Antibodies To Expressionmentioning
confidence: 90%
“…Previous high-throughput strategies have relied on mouse (Endlich et al 2002;Brunskill et al 2011;Jain et al 2011) or human (Saleem et al 2008) immortalized glomerular visceral epithelial cells, but in vitro culture leads to rapid loss of both lineagespecific phenotypes and lineage-specific gene expression. Wholetissue-based molecular profiles of renal disease are attainable Higgins et al 2004;Schmid et al 2006;Bennett et al 2007;Ju et al 2009;Hodgin et al 2010;Lindenmeyer et al 2010;Woroniecka et al 2011) since human renal tissue is routinely obtained by diagnostic fine needle biopsy, but wholetissue expression profiles have not previously been capable of identifying gene expression at the cell-lineage level. This difficulty is not unique to renal disease.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Comprehensive evaluations were performed and reported elsewhere on various medical factors of the patients (18), and it is unlikely that these factors have confounded age-regulated changes in gene expression (18,21). Only cortex samples (72 in total) were used in our analysis.…”
mentioning
confidence: 99%